(285) صناعة الرخام فى مصر" الواقع والمأمول " بالتطبيق علي " المنطقة الصناعية بشق الثعبان" Marble Industry in Egypt "Reality and Hope" with Application in "Shaq Al-Taeban Industrial Zone" - إيمان احمد الشربينى; ممدوح الشرقاوى; محمد نصر فريد; زلفى شلبى; سمير عريقات; واخرون (معهد التخطيط القومى, 2022)
Egypt is considered as an inexhaustible store for all kinds of ornamental stones, including marble, granite, and diorite. Moreover, there are many other stones of historical fame - such as porphyry, breccias serpentine and alabaster - that are highly demanded at all markets all over the world. Ornamental stones are considered one of the most important mining sources in Egypt, due to diversity of sources, kinds, and the huge reserves available. The importance of the ornamental stones industry stems from the availability of different bases, such as the historical fame, the resistance of deterioration factors across ages, the distinguished geographical location of Egypt, and its closeness to export markets. Most importantly, however, is the availability of a distinguished industrial area containing many factories and workshops for cutting and polishing marble and granite, that is the area of “Shaq-al-Thoban”, which enjoys high rates of mining production. In fact, Egypt ranked the fifth in the field of ornamental stones, where modern technologies are available for some factories, which achieve high levels of quality. /